Effect of Pectin Coating Enriched With Oregano Essential Oil on the Fresh-Cut Papaya Quality - Abdullah, Ts Dr Norazlin (Enhanced Knowledge in Sciences and Technology, 2022)
Fresh-cut papaya has been found to deteriorate more readily than intact fruit resulting in increased surface browning, water loss, textural breakdown and off-flavor growth. Thus, the purpose of this study was to evaluate the effect of coating the fresh-cut papaya with pectin and oregano essential oil on its physicochemical properties during storage at 4°C for 12 days. Yeast and molds growth as well as sensory evaluation were also done in this study. The incorporation of oregano (Origanum vulgare) essential oil to the pectin coating has improved the physicochemical qualities of the fresh-cut papaya by having the quality changes of up to 34% only compared to the control samples, which able to achieve up to 75% quality changes. The fresh-cut papaya coated with 2.25% of pectin and 0.75% OEO still under the critical limit of yeast and moulds growth even has been stored for 12 days at 4°C, while the uncoated fresh-cut papaya has passed the critical limit at day 8 of storage. Although the coated fresh-cut papaya was accepted by the panellists, future research on the removal of unacceptable odour from the coatings may be needed to improve the sensorial quality of the coated papaya.